A PATIENT WITH ACUTE CORONARY SYNDROME WITHOUT ST-SEGMENT ELEVATION AND CONSERVATIVE MANAGEMENT. PHARMACOLOGICAL OPTIONS TO IMPROVE PROGNOSIS - O. L. Barbarash; V. V. Kashtalap (Медицинский совет, 2017)
The original article tells about the key aspects that characterize the problem of acute coronary syndrome without ST-segment elevation (ACSWSTE) in the Russian Federation: high prevalence, current approaches to risk assessment of early and long-term adverse outcomes and diagnostic challenges. Based on the data from the All-Russian Register RECORD-3, the main factors limiting the effectiveness of treatment of patients with ACSWSTE are highlighted: underestimated relevance of risk calculators (GRACE) and biological markers for myocardial necrosis by practicing physicians who manage these patients, underutilization of invasive treatment, failure to prescribe drugs that improve prognosis, including dual antiplatelet therapy in patients with conservative management. The prospects for the use of ticagrelor (Brilinta) to improve short- and long-term prognosis of the disease are estimated.